The Impact of Covid 19 Pandemic on the Cattle Sales - Resolinda Harly; Sri Mulyani (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2022)
The Covid-19 pandemic has changed the order of life and affected all sectors of life, including the livestock sub-sector. Minister of Agriculture Syahrul Yasin Limpo (2020) stated that the need for cattle farming in Indonesia reaches 700 thousand tons, while the existing livestock can only meet the needs of 400 thousand tons. This means that cattle farming still has a great opportunity to develop. Based on data, existing cattle farms are dominated by smallholder farms (97.7%). This study aims to see how the condition of smallholder cattle farms during the pandemic in terms of; 1. How is the level of cattle sales during the pandemic, 2. Maintenance system. The research design used in this study was a survey method conducted in the district of 50 cities of Lareh Sago Halaban. Sampling was carried out by purposive random sampling method. The results of research conducted on smallholder cattle farms during the pandemic on sales at the beginning of the pandemic in March-May 2020, are 56% in the following three months June-August 2020 as many as 52% in the third of Sept-Nov 2020 is 96% and at 52% for the month of Dec-Feb 2021. Sales are also influenced by policies taken by the government at the regional level. The cattle rearing system has been 72% intensively carried out by farmers, the availability of forage is still at a sufficient level for a cattle scale of 1-3 heads, but more than that amount if farmers do not have grass land is not sufficient. The cattle business during the pandemic can still run well and can be used as a business opportunity for youth.